Diagnostic performance of visible severe wasting for identifying severe acute malnutrition in children admitted to hospital in Kenya - Mogeni, Polycarp (World Health Organization, 2011)
OBJECTIVE: To determine the diagnostic value of visible severe wasting in identifying severe acute malnutrition at two public hospitals in Kenya. METHODS: This was a cross-sectional study of children aged 6 to 59.9 months admitted to one rural and one urban hospital. On admission, mid-upper arm circumference (MUAC), weight and height were measured and the presence of visible severe wasting was assessed. The diagnostic performance of visible severe wasting was evaluated against anthropometric criteria. FINDINGS: Of 11 166 children admitted, 563 (5%) had kwashiorkor and 1406 (12.5%) were severely wasted (MUAC < 11.5 cm). The combined sensitivity and specificity of visible severe wasting at the two hospitals, as assessed against a MUAC < 11.5 cm, were 54% (95% confidence interval, CI: 51–56) and 96% (95% CI: 96–97), respectively; at one hospital, its sensitivity and specificity against a weight-for-height z-score below −3 were 44.7% (95% CI: 42–48) and 96.5% (95% CI: 96–97), respectively. Severely wasted children who were correctly identified by visible severe wasting were consistently older, more severely wasted, more often having kwashiorkor, more often positive to the human immunodeficiency virus, ill for a longer period and at greater risk of death. Visible severe wasting had lower sensitivity for determining the risk of death than the anthropometric measures. There was no evidence to support measuring both MUAC and weight-for-height z-score. CONCLUSION: Visible severe wasting failed to detect approximately half of the children admitted to hospital with severe acute malnutrition diagnosed anthropometrically. Routine screening by MUAC is quick, simple and inexpensive and should be part of the standard assessment of all paediatric hospital admissions in the study setting.